Role of colour Doppler in predicting foetal outcome in maternal anaemia - Alka Agrawal; Gaurav Bhandari; Silky Taya; Vinod Chaudhary (Journal of Family Medicine and Primary Care)
Context: Anaemia is the most common nutritional deficiency in Indian pregnant females. It ensues foetal hypoxia resulting in different compensatory mechanisms in the foetus which may result in adverse perinatal outcomes. Colour Doppler can be used to measure these hemodynamic changes of the foetus ahead of the clinical manifestations, guiding the obstetrician for the appropriate management and circumventing any dire complication. Aims: The aim of this study is to detect foetal haemodynamic changes associated with maternal anaemia and assess the parameters which predict these changes accurately. Settings and Design: Prospective cohort study. Materials and Methods: Two hundred and forty pregnant females in the third trimester, divided into four groups based on their haemoglobin levels in the non-anaemic, mild, moderate and severe anaemic groups, were included in the study. These patients were followed up for foetal outcome in terms of effective foetal weight, APGAR score and neonatal intensive care unit admission. Statistical Analysis Used: Analysis of Variance Appearance, Pulse, Grimace, Activity and Respiration (ANOVA) test was used to compare the quantitative variables. SPSS software was used. Results: The middle cerebral artery (MCA) Doppler indices and cerebroplacental ratio (CPR) values were increasing while umbilical Doppler indices were decreasing with the increasing severity of anaemia. CPR was found to be the most sensitive predictor for foetal outcome. Conclusions: Maternal anaemia results in foetal hypoxia which can be measured in terms of foetal Doppler indices. CPR was found to be more sensitive than the umbilical or MCA in predicting foetal hypoxia and in turn the perinatal outcome of foetuses of anaemic pregnant females. The foetuses with low CPR values will require urgent intervention to improve the outcomes.